Cross-functional Business Processes as a new research object - E. I. Gordeeva (Учёт. Анализ. Аудит)
Recent research in business process management has shown the negative impact of various kinds of barriers on the financial performance of the organization, arising from the inconsistency of the actions of individual business units. Academicians and practitioners develop proposals for creating a cross-functional team of employees within the company to eliminate such barriers. Despite the intensification of scientific research in the field of business process optimization in recent years, the task of improving accounting methods and analyzing the effectiveness of business processes remains relevant. The study used such methods of scientific knowledge as: observation, comparison, analysis, modeling, as well as a systematic approach. Data processing, their systematization and analysis were carried out using the MS Excel program. The scientific novelty of the work lies in the systematization of existing knowledge in management accounting and controlling business processes, the allocation of a new object of research —  cross-functional business processes. The theoretical significance of the study is an improvement of the conceptual apparatus and methodology of cross-functional business processes management. Of practical importance are the system of indicators for evaluating the effectiveness of cross-functional business processes, recommendations for the implementation of management accounting and controlling systems for cross-functional business processes, as well as assessing their consistency based on a barrier map.